Anchoscelis fuscomixta noravanka, a new subspecies from Armenia (Lepidoptera: Noctuidae: Noctuinae) - Saldaitis, Aidas; Dûda, Juozas; Volynkin, Anton V.; Kalashian, Mark (Zootaxa, 2022)
A new subspecies of the genus Anchoscelis Guenée, 1839, Anchoscelis fuscomixta noravanka ssp. n. is described from south-west Armenia. The new subspecies belongs to the nominate subgenus of Anchoscelis and is similar, besides Anchoscelis fuscomixta (Gyulai & L. Ronkay, 2006), to Anchoscelis pauli (Staudinger, 1892), Anchoscelis kindermanni (Fischer von Röslerstamm, 1839) and Anchoscelis consueta (Herrich-Schäffer, 1852). Adults and male and female genitalia of the new subspecies and the similar taxa are illustrated. The habitat of the new subspecies is characterised and illustrated.